Gas‐phase rate coefficients for a series of alkyl cyclohexanes with OH radicals and Cl atoms. Issue 8 (6th June 2018) - Bejan, Iustinian G.; Winiberg, Frank A. F.; Mortimer, Nicholas; Medeiros, Diogo J.; Brumby, Charlotte A.; Orr, Stephanie C.; Kelly, Jamie; Seakins, Paul W.
Abstract: The rate coefficients of the reactions of OH radicals and Cl atoms with three alkylcyclohexanes compounds, methylcyclohexane (MCH), trans‐ 1, 4‐dimethylcyclohexane (DCH), and ethylcyclohexane (ECH) have been investigated at (293 ± 1) K and 1000 mbar of air using relative rate methods. A majority of the experiments were performed in the Highly Instrumented Reactor for Atmospheric Chemistry (HIRAC), a stainless steel chamber using in situ FTIR analysis and online gas chromatography with flame ionization detection (GC‐FID) detection to monitor the decay of the alkylcyclohexanes and the reference compounds. The studies were undertaken to provide kinetic data for calibrations of radical detection techniques in HIRAC. The following rate coefficients (in cm 3 molecule −1 s −1 ) were obtained for Cl reactions: k (Cl+MCH) = (3.51 ± 0.37) × 10 –10, k (Cl+DCH) = (3.63 ± 0.38) × 10 −10, k (Cl+ECH) = (3.88 ± 0.41) × 10 −10, and for the reactions with OH radicals: k (OH+MCH) = (9.5 ± 1.3) × 10 –12, k (OH+DCH) = (12.1 ± 2.2) × 10 −12, k (OH+ECH) = (11.8 ± 2.0) × 10 −12 . Errors are a combination of statistical errors in the relative rate ratio (2σ) and the error in the reference rate coefficient. Checks for possible systematic errors were made by the use of two reference compounds, two different measurement techniques, and also three different sources of OH were employed in this study: photolysis of CH3 ONO with black lamps, photolysis of H2 O2 at 254 nm, and nonphotolytic trans ‐2‐butene ozonolysis. For DCH, some direct laser flash photolysis studies were also undertaken, producing results in good agreement with the relative rate measurements. Additionally, temperature‐dependent rate coefficient investigations were performed for the reaction of methylcyclohexane with the OH radical over the range 273‐343 K using the relative rate method; the resulting recommended Arrhenius expression is k (OH + MCH) = (1.85 ± 0.27) × 10 –11 exp((–1.62 ± 0.16) kJ mol −1 / RT ) cm 3 molecule −1 s −1 . The kinetic data are discussed in terms of OH and Cl reactivity trends, and comparisons are made with the existing literature values and with rate coefficients from structure‐activity relationship methods. This is the first study on the rate coefficient determination of the reaction of ECH with OH radicals and chlorine atoms, respectively.